Toward a Smart Campus: A Qualitative Study of the Digital Learning Ecosystem Model in Indonesian Higher Education - Stefani Made Ayu Artharini Koesanto; Gunawan Wiradharma; Mario Aditya Prasetyo; Arina Rubyasih; Enang Rusyana; Karina Pramita Ningrum (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to describe the implementation of innovative campuses in Indonesia based on a digital learning ecosystem model, while also analyzing how universities leverage technology to foster institutional innovation and support the development of a Smart Campus framework. This research employed a descriptive qualitative approach by conducting interviews with lecturers and students from several universities in Indonesia, including Makassar State University, Pontianak State Polytechnic, IPB University, Gadjah Mada University, Budi Luhur University, and Multimedia Nusantara University. Data were collected through semi-structured in-depth interviews using an interview protocol that focused on technology utilization, system integration, digital literacy, and organizational readiness. The data were analyzed using thematic analysis to identify recurring patterns in the implementation of Smart Campus initiatives. The findings reveal that the implementation of Smart Campus in Indonesian universities remains partial and fragmented due to limited system integration, unequal technological infrastructure, and varying levels of digital readiness among academic staff. These findings indicate that developing a sustainable Digital Learning Ecosystem requires not only the provision of technological infrastructure but also strong institutional alignment, continuous digital literacy development, and the design of integrated digital platforms.